Limited Si-nutrient status of rice plants in relation to plant-available Si of soils, nitrogen fertilizer application, and rice-growing environments across Sub-Saharan Africa - Tsujimoto, Y.; Muranaka, S.; Saito, Kazuki; Asai, H. (Elsevier, 2014)
Rice is a specific silica-accumulator among higher plants. The Si in rice enhances resistance to biotic and abiotic stresses. The booming demand for rice in Sub-Saharan Africa (SSA) requires rapid increases in rice production, and hence more Si supply will be needed from soils, irrigation water, and external inputs. However, the current Si-nutrient status of rice plants and relevant factors has been so far paid little attention in the region. Therefore, an extensive survey was conducted for evaluating variability of Si concentration in rice straw in relation to soil properties, fertilizer management practices, and rice-growing environments across a wide range of local farmers’ fields in SSA. Plant and soil samples were collected at harvesting time from 99 fields in Benin, Ghana, Guinea, Kenya, Madagascar, Mozambique, and Nigeria, and then chemically analyzed. The Si concentration in straw ranged 1.7–8.4%, and the values in 68% of the fields were below the critical deficiency level of 5%. The Si concentration in straw was most significantly correlated with the amounts of water-soluble Si in soils after 1-week anaerobic incubation at 40 °C (hereafter, plant-available Si). The plant-available Si was particularly low in the acidic soils of Highland and Humid Agro-ecological zones, mainly consisting of weathered Oxisols and Ultisols. The mean Si values were greatest in the order of irrigated lowland (5.3%) > rainfed lowland (4.3%) > upland (3.4%) among different rice-growing environments. Multiple regression analysis revealed that 59% of the variation in Si concentration in straw was explained by the plant-available Si in soils, rice-growing environments, N application rates, and mineralizable N in soils. The regression model indicated that improvement of plant-available Si in soils could increase the Si concentration in straw at a rate of 0.043% per mg kg−1, while external N application lowered the Si concentration in straw at a rate of 0.0068% per kg N ha−1 input. This extensive survey revealed that low Si nutrient status was widely observed for rice as associated with limited plant-available Si in the SSA soils. The probability of Si deficiency can be increased with abundant N application and non-submerged field conditions. By focusing on these Si-deficient field conditions, further studies should quantify the relationship between Si-nutrient status and occurrence of environmental stresses such as blast infection so as to develop appropriate Si-management practices for rice production in SSA.